Preliminary evidence of prolonged timing effects of theta-burst stimulation in the reading system - Harrington, Rachael M.; Krishnamurthy, Lisa C.; Ossowski, Alexandra; Jeter, Mykayla; Davis, Adriane; Bledniak, Ewelina; Ware, Ashley L.; Morris, Robin; Arrington, C. Nikki (Frontiers in Human Neuroscience, 2023)
This novel study provides the first examination of whether the timing and facilitation effects of intermittent and continuous theta burst stimulation influence the reading network. We investigated the broad inhibitory and excitatory theta-burst stimulation effects on reading outcomes and how timing post-stimulation affects change in reading behavior. We showed that time post-stimulation, but not type of stimulation, has a significant effect on reading behavior. This study has implications for understanding the effects of theta-burst stimulation in the reading and language systems. It also has implications for theta-burst stimulation study design. Specifically, our results provide evidence of a lack of dissociation between inhibition and excitation stimulation paradigms for reading behavior and when after stimulation outcome measures should be collected.